Video tutorials: an expanding audiovisual genre - Gianna Tarquini; Richard E. McDorman (JoSTrans: The Journal of Specialised Translation)
With video-based learning genres (e.g. MOOCs, the flipped classroom and tutorials) increasingly gaining momentum in formal and informal education, accessibility needs become a crucial challenge for ensuring inclusive learning among diverse audiences, both locally and internationally. This paper aims to shed light on unexplored linguistic and audiovisual features of video tutorials by looking at instruction as a multimodal instance of communication. Using the official PowerPoint tutorials as the basis of a pilot study, we propose a model for the conceptualisation of semiotic resources, along with translation analysis of multilingual versions, specifically an original U.S. English version, an Italian translation with interlingual subtitles (partial localisation) and a French adaptation (full localisation). Results describe the benefits of using intralingual subtitles and best practices for enhancing the accessibility and internationalisation of video tutorial content, with interlingual subtitles deemed a less effective translation method. Finally, adaptation techniques are described in their semiotic dimensions of re-creation and transcreation, suggesting possible ways in which audiovisual translation theories and methods can contribute to the design of video-based learning content for international learners.